17.7k views
4 votes
Simplify sin^2y/sec^2 y−1 to a single trigonometric function

1 Answer

10 votes

Answer:


\frac{ { \sin}^(2) y}{ { \sec}^(2)y - 1 } = { \cos }^(2) y

Explanation:

We know that
{ \tan }^(2) y = { \sec }^(2) y - 1

Also ,
{ \tan}^(2) y = \frac{ { \sin }^(2) y}{ { \cos }^(2)y }

So ,


\frac{ { \sin }^(2)y }{ { \sec }^(2)y - 1 } = \frac{ { \sin}^(2) y}{ { \tan }^(2) y} = \frac{ { \sin }^(2)y }{ \frac{ { \sin}^(2) y}{ { \cos}^(2)y } } = { \cos }^(2) y

User Neurozen
by
4.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.